Morse Code Communication Aid for the Handicapped - Callway, E.G. (My University, 1981)
A microprocessor driven display was built and programmed for the storage and reproduction of Bliss symbols. An explanation is offered for the success of the symbol language in teaching the handicapped.
The hardware was designed to be inexpensive enough for classroom use, but still deliver adequate flexibility and resolution. Due to the complexity and variety of the symbols a method of data compaction was developed to reduce the required storage space.
Initial tests are presented and suggestions are made for continuing the work.
Keywords: engineering physics; Morse code; communication aid; handicapped